0382 Increasing male/female inequalities in rates of workplace violence in ontario between 2002 and 2014: a comparison of two data sources. (21st August 2017) - Smith, Peter; Chen, Cynthia
Abstract : Literature examining male/female differences in rates of workplace violence has produced mixed findings. This study examined trends in rates of workplace violence using two population level data sources. These were: workers' compensation claims for assaults that required time off work; and emergency department visits for assaults or accidental contact from another person, where the treating physician determined that the payer should be workers' compensation. For both data sources, denominator information of the population at risk was generated by sex, age groups and time period using the Labour Force Survey. Over the period 2002 to 2014 rates of assault among men remained stable, from 31.5 per 100, 000 FTEs to 32.5 per 100, 000 FTEs. Conversely among women rates of lost-time claims due to workplace violence increased from 38.9 per 100, 000 FTEs to 59.1 per 100, 000 FTEs - an absolute increase of 20.2 assaults per 100, 000 FTEs, and a relative increase of 52%. These divergent trends were mirrored in the emergency department records, with rates of ED presentations among men remaining stable between 2004 and 2014 (38.2 to 39.8 per 100, 000 FTEs); while among women rates of presentation increased from 34.9 per 100, 000 FTEs to 52.9 per 100, 000 FTEs - a relative increase of over 50%. In both time periods rates of assaults were relatively stable for men and women up till about 2008/09, after which point rates diverged between men and women. Using two data sources this study demonstrates increasing male/female inequalities in workplace violence in Ontario.